The endogenous thrombin potential in patients with left ventricular assist device or heart transplant - Schlagenhauf, Axel; Haidl, Harald; Trummer, Georg; Berchtold-Herz, Michael; Pooth, Jan-Steffen; Strini, Tanja; Geisen, Ulrich; Beyersdorf, Friedhelm; Zieger, Barbara (Frontiers in Medicine, 2023)
Background The Heartmate 3 (HM 3) is a left ventricular assist device featuring less shear stress, milder acquired von Willebrand syndrome, and fewer bleeding incidences than its predecessor the Heartmate II (HM II). The novel surface coating of the HM 3 suggests less contact activation of plasmatic coagulation. We hypothesized that patients with HM 3 exhibit fewer aberrations in their thrombin potential than patients with HM II. We compared these results with the thrombin potential of patients with heart transplantation (HTX). Methods Thrombin generation in plasma samples of patients with HM II (n = 16), HM 3 (n = 20), and HTX (n = 13) was analyzed 3 days after implantation/transplantation and after long-term support (3–24 months) with HM II (n = 16) or HM 3 (n = 12) using calibrated automated thrombography. Heparin in postoperative samples was antagonized with polybrene. Results Three days postoperatively HM II patients exhibited a lower endogenous thrombin potential (ETP) than HM 3 and HTX patients (HM II: 947 ± 291 nM*min; HM 3: 1231 ± 176 nM*min; HTX: 1376 ± 162 nM*min, p < 0.001) and a lower velocity index of thrombin generation (HM II: 18.74 ± 10.90 nM/min; HM 3: 32.41 ± 9.51 nM/min; HTX: 37.65 ± 9.41 nM/min, p < 0.01). Subtle differences in the thrombin generation profiles remained in HM II and HM 3 patients under long-term support (Velocity Index: HM II: 38.70 ± 28.46 nM/min; HM 3: 73.32 ± 32.83 nM/min, p < 0.05). Prothrombin fragments 1 + 2 were higher in HM II than in HM 3 patients (HM II: 377.7 ± 208.4 pM; HM 3: 202.1 ± 87.7 pM, p < 0.05) and correlated inversely with the ETP (r = −0.584, p < 0.05). Conclusion We observed a more aberrant thrombin generation in HM II than in HM 3 despite comparable anticoagulation and routine parameters. A trend toward lower values was still observable in HM 3 compared to HTX patients. Calibrated automated thrombography may be a good tool to monitor the coagulation state of these patients and guide anticoagulation in the future.